Improved Marketing Performance and Product Innovation for The Optimization of Competitive Advantage - Harianto Harianto; Sri Rahayu; Megasari Gusandra Saragih (AIBPM Publisher, 2019)
This research analyses on improving marketing performance and product innovation for the optimization of competing excellence. Sample amounted to 100 customers of UKM Dodol workshop of the Perbaungan Serdang Regency Bedagai by using SPSS Analysis tool version 19.0. The results showed that the marketing performance and product innovations have significant effect on the competitive advantage of UKM Dodol workshop of Serdang Regency Bedagai.